Wpływ zmęczenia stawu skokowego na pracę systemu kontroli postawy ciała = The influence of the ankle joint’s fatigue on functioning of postural control system - Pyskir, Małgorzata; Piela, Cyryl; Ratuszek-Sadowska, Dorota; Pyskir, Jerzy; Trela, Ewa; Hagner, Wojciech (Journal of Education, Health and Sport, 2016)
Pyskir Małgorzata, Piela Cyryl, Ratuszek Dorota, Pyskir Jerzy, Trela Ewa, Hagner Wojciech. Wpływ zmęczenia stawu skokowego na pracę systemu kontroli postawy ciała = The influence of the ankle joint’s fatigue on functioning of postural control system. Journal of Education, Health and Sport. 2016;6(8):567-580. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.609942 http://ojs.ukw.edu.pl/index.php/johs/article/view/3784 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016. Wpływ zmęczenia stawu skokowego na pracę systemu kontroli postawy ciała The influence of the ankle joint’s fatigue on functioning of postural control system Małgorzata Pyskir1,Cyryl Piela2, Dorota Ratuszek1, Jerzy Pyskir3, Ewa Trela1, Wojciech Hagner1 Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Orvit Clinic, Toruń Katedra i Zakład Biofizyki, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie Wstęp Za charakterystyczną dla człowieka pozycję spionizowaną i stabilność podczas poruszania się odpowiada system kontroli postawy. Analizuje on informacje ze środowiska zewnętrznego i wysyła do mięśni sygnały umożliwiające reakcje na bodźce destabilizujące. Staw skokowy stanowi jedną z ważniejszych struktur odpowiedzialnych za funkcjonowanie tego systemu. Cel pracy W niniejszej pracy analizowano wpływ zmęczenia mięśni obsługujących staw skokowy na stabilność sylwetki podczas swobodnego stania. Materiał i metody W badaniach wzięło udział 32 ochotników w wieku 18-25 lat w tym 17 kobiet i 15 mężczyzn. Nikt nie zgłaszał kontuzji stawu skokowego w ciągu ostatnich 3 miesięcy. Do badania wykorzystano posturograf firmy PROMED J. Otton. Platforma rejestruje błądzenie centrum nacisku (COP) na podłoże w czasie swobodnego stania przez 30 sekund. Badanie wykonuje się dwukrotnie – przy oczach otwartych, a następnie przy zamkniętych. Bezpośrednio po pierwszym, wstępnym pomiarze badana osoba wykonała 50 wspięć na palce prawej stopy, po czym powtarzano pomiar posturograficzny. Wyniki Analizowano wartości średniego promienia, pola powierzchni rozwiniętej oraz długości statokinezjogramu. Prawie wszystkie wartości parametrów postrurograficznych uzyskiwane przy oczach otwartych byłynistotnie mniejsze niż wartości uzyskiwane przy oczach zamkniętych, co jest zgodne z obserwacjami innych autorów. Po wykonaniu wspięć wartości badanych parametrów istotnie wzrosły, co świadczy o gorszej stabilności sylwetki niż w badaniu wstępnym. Wnioski Zmęczenie mięśni obsługujących prawy staw skokowy górny poprzez wykonanie 50 wspięć na palce w istotny sposób pogarsza stabilność postawy, co zwiększa ryzyko niekontrolowanych upadków. Wydaje się celowe przeprowadzenie szerszych badań tego tematu analizując codzienną aktywność fizycznej badanych. Słowa kluczowe: system kontroli postawy, staw skokowy, posturograf. Abstract Introduction Characteristic for human body vertical position and stabilization during the move ensures a postural control system. Its role is to analyse the information from the internal and external environment and send the signal to the muscles in order to react of destabilizing stimuli. Ankle joint is one of the most important structures responsible for the system functioning. Aim of srtudy The aim of this dissertation was to investigate the influence of fatigue on muscles operating the ankle joint on profile stabilization during the free stand. Materials and methods The study involved 32 volunteers in age from 18 to 25, including 17 women and 15 men. Nobody has reported the ankle joint contusion during last three months. The PRO-MED J. Olton company stabilometric platform was used in test . The platform registers the centre of pressure (COP) on the ground while free stand for 30 seconds. The test was made twice - with open and closed eyes. Directly, after the first, initial measurement tested person did 50 climbs on right foot toes therewith the measurement was repeated. Results The values of average radius, the field of developed surface and the length of statokinesiogram were analysed. The magnitude of measured parameters obtained for open eyes were greater than values from closed eyes test, which is consistent with observation of the other authors. After the climb values investigated parameters significantly increased which proves a lower profile stabilization than during the initial test. Conclusions The importance of muscles that support ankle joint by making 50 climbs on toes deteriorates the postural stabilization in crucial way which increases the risk of uncontrolled falls. Conduct further research on this topic with analyse the everyday physical activity seems to be expendient. Key words: postural control system, ankle joint, stabilometric platform.